An introduction to the natural system of botany = or, A systematic view of the organisation, natural affinities, and geographical distribution, of the whole vegetable Kingdom - Lindley, John 1799-1865 (Cambridge University Press, 2015)
Employed early in his career by Sir Joseph Banks, the botanist John Lindley (1799-1865) is best known for his recommendation that Kew Gardens should become a national botanical institution, and for saving the Royal Horticultural Society from financial disaster. As an author, he is best remembered for his works on taxonomy and classification. A partisan of the 'natural' system of Jussieu rather than the Linnaean, Lindley writes, in his preface to this 1830 work, that it was originally created for his own use, to avoid having recourse to 'rare, costly and expensive publications' available only in the libraries of the wealthy. His intention is to give a 'systematic view of the organisation, natural affinities, and geographical distribution of the whole vegetable kingdom', as well as of the uses of plants 'in medicine, the arts, and rural or domestic economy'. The work is important in the history of taxonomy.